Letter to the Editor from Colle et al. Issue 6 (23rd June 2021) - Colle, Raphael; Andre, Thierry; Menu, Yves
Abstract : In their article, Fucà et al highlight that early tumor shrinkage and depth of response predict the prognosis of patients with metastatic colorectal cancer (mCRC) microsatellite instability (MSI-H)/deficient mismatch repair (dMMR) treated by immune checkpoint inhibitors (ICI). We are surprised that no cases of pseudoprogression (PSPD) were reported in their study. PSPDs were described under ICI in patients treated for MSI/dMMR mCRC. In a cohort of 123 patients treated with anti-PD1±antiCTL-4 for MSI/dMMR mCRC, we reported 12 patients with PSPD, representing 10% of the cohort. Of 12 patients with PSPD, 8 secondary achieved an objective response and were alive and free of progression at the data lock. Conversely, in Fucà's article, no PSDP was observed and the patients with primary radiological progression (21.7%) had a poor overall survival. These differences between the two series could be probably explained by the following points. First, Fucà et al use RECIST 1.1 criteria for radiological evaluation. Second, the first imaging was done after 8–9 weeks of treatment in Fucà's article, which may be late to detect PSPD. In conclusion, if the first evaluation is made during the first 3 months of treatment, using iRECIST criteria seems mandatory to avoid stopping treatment prematurely, especially in patients receiving anti-PD1 alone.